Staged seduction selling dreams in a Tokyo host club - Takeyama, Akiko 1970- (Stanford, California Stanford University Press, 2016)
This manuscript provides a window into the Japanese nighttime bars where male hosts seduce their female clients and entice them to spend money. It attempts to answer questions such as: what happens when women are the financial providers and men are the paid seducers? How do they communicate when women want to be seduced but cannot say so? What is it like to be in a commodified form of romance? Takeyama investigates various aspects of the host clubs including the host club as workplace, the hosts themselves, the women who frequent host clubs, the club managers, and the ethics of host club deception. Ultimately, the book provides readers with an extraordinary look into the dynamics of seduction, and the broader dynamics of the contemporary Japanese political economy.--Publisher's description
Introduction : promise of the future -- The consumable city -- Commodified romance -- Entrepreneurial attraction -- Feminine restoration -- The art of seduction -- Conclusion : affect economy.
Includes bibliographical references (pages 195-208) and index.
Keywords: Love -- Economic aspects -- Japan -- Tokyo; Man-woman relationships -- Japan -- Tokyo; Sex-oriented businesses -- Japan -- Tokyo; Sexual ethics -- Japan -- Tokyo; Nightclubs -- Japan -- Tokyo; Tokyo (Japan) -- Social life and customs -- 21st century